Pendampingan bagi Pengembangan Anak Berkebutuhan Khusus dalam Lingkungan Inklusif - Situmorang, Irvan Rolyesh; Putri, Cantika; Rahmadini, Dara Aisyah; Lie, Sharlen; Koscius, Rendy; Wilson, Wilson (Ali Institute of Research and Publication, 2025)
This community service activity was carried out to support the strengthening of inclusive education through a mentoring program for children with special needs at RA Aisyah Azzahra class B Makkah. The background of this activity was the discovery of various obstacles in the implementation of inclusive learning, particularly related to limitations in attention span, understanding of instructions, and social interaction skills of children with special needs in heterogeneous classes. The approach used was descriptive qualitative with data collection techniques including direct observation, interviews with teachers, and documentation of activities. The mentoring program was carried out through individual mentoring during the learning process and group mentoring through collaborative play activities. The results of the activities showed an increase in children's learning engagement, better responses to teacher instructions, and early development in social aspects and behavior control. In addition to benefiting children with special needs, these activities also strengthened teachers' understanding of the importance of flexible mentoring strategies tailored to the needs of students. In general, these activities made a practical contribution to supporting the implementation of inclusive education and have the potential to be developed in similar educational units.